OC-045 Reduced Risk Of Emergency Admission For Colorectal Cancer Associated With Introduction Of Bowel Cancer Screening Across England: Retrospective National Cohort Study. (9th June 2014) - Geraghty, J; Shawihdi, M; Thompson, E; Sarkar, S; Pearson, M; Bodger, K
Abstract : Introduction: We examined whether roll out of the bowel cancer screening programme (BCSP) across England was associated with a reduced risk of emergency hospital admission for people presenting with colorectal cancer (CRC) during this period. Methods: Design: Retrospective cohort study of 27, 763 incident cases of CRC over a 1-year period during the roll-out of screening across parts of England. Primary outcome: Emergency (unplanned) hospital admission during diagnostic pathway. Primary exposure: Living in an area where BCSP was active at the time of diagnosis. Patients were categorised into three exposure groups: BCSP not active (reference group), active <6 months or active ≥6 months. To explore confounding we studied risk of emergency admission for cases of oesophagogastric cancer using the same design. Results: Risk of emergency admission for CRC in England was associated with increasing age, female gender, co-morbidity and social deprivation. After adjusting for these factors in logistic regression, the odds ratio for emergency admission in patients diagnosed ≥6 months after start-up of local screening was 0.83 (CI: 0.76–0.90). The magnitude of risk reduction was greatest for cases of screening age (OR 0.75; CI: 0.63–0.90) but this effect was apparent also for cases outside the 60–69 year age-group (OR 0.85; CI: 0.77–0.94). Living in an area with active BCSP conferred no reduction in risk of emergency admission for people diagnosed with oesophagogastric cancer during the same period. Conclusion: The start-up of bowel cancer screening in England was associated with a substantial reduction in risk of emergency admission for CRC in people of all ages. This suggests that the roll-out of the programme had early and indirect benefits beyond those related directly to participation in screening. Disclosure of Interest: J. Geraghty Grant/research support from: Cook Medical, M. Shawihdi: None Declared, E. Thompson: None Declared, S. Sarkar: None Declared, M. Pearson: None Declared, K. Bodger: None Declared.